2020
DOI: 10.32539/dies.v1i1.28
|View full text |Cite
|
Sign up to set email alerts
|

Terapi Maksimal Medikamentosa pada Rinosinusitis Kronis

Abstract: ABSTRAKRinosinusitis kronis (RSK) merupakan kumpulan gejala dan tanda yang dapat timbul dari berbagai etiologiyang berbeda. Peradangan mukosa yang terus- menerus dan lendir yang kental sering menyebabkan gejala-gejala post nasal drip, hidung tersumbat, penurunan indra penciuman dan atau nyeri tekan wajah. Etiologi pastiRSK masih belum diketahui dan bersifat multifaktorial, dan tidak ada mekanisme molekul tunggal yangmenjelaskan cedera dari perubahan jaringan. Terapi maksimal medikamentosa (MMT) adalah standarp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(20 reference statements)
0
1
0
1
Order By: Relevance
“…A recent study found biofilms on the mucosa of 75% of patients undergoing surgery for chronic rhinosinusitis. [30] Health-related quality of life has been identified as a goal for all people at all stages of life by leading health organizations. Health-related quality of life, relative to a person's health or disease status, concerns policymakers, researchers, and healthcare practitioners.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent study found biofilms on the mucosa of 75% of patients undergoing surgery for chronic rhinosinusitis. [30] Health-related quality of life has been identified as a goal for all people at all stages of life by leading health organizations. Health-related quality of life, relative to a person's health or disease status, concerns policymakers, researchers, and healthcare practitioners.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indikasi relatif tindakan ini adalah rinosinusitis kronis atau rinosinusitis simptomatik rekuren dan polip nasi simptomatik yang tidak respon dengan medikamentosa. 31…”
Section: Hasil Penelitianunclassified